SURVEILLANCE OF PULMONARY TUBERCULOSIS CASES IN SPECIAL PLACES (ISLAMIC BOARDING SCHOOL/PESANTREN) BANGKA SELATAN, BANGKA BELITUNG - Juhaina, Ena; Aurora, Wahyu Indah Dewi (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2023)
ABSTRACTBackground: Pulmonary tuberculosis is one of the infectious and contagious diseases with the highest prevalencein the world. Tuberculosis is a major public health problem with the third largest number in the world after Chinaand India, accounting for around 10% of the total number of tuberculosis patients in the world. The purpose of thissurveillance is to study the discovery of new TB cases and monitoring of treatment at a Special Place in SouthBangka Regency).Method: This study uses a cross-sectional study design carried out in May 2022. The population of this study isthe students of the Islamic Boarding School in South Bangka Regency. The sample in this study were 47respondents with a history of coughing in the last 2 weeks. Primary data collection was in the form of collectingsputum from respondents who indicated symptoms of pulmonary TB. Interviews by filling out questionnaires torespondents.Result: Based on the results of the examination using the TCM method, there were no positive TB samples.Conclusion: Community Health Center TB officers increase promotive and preventive efforts, especially forstudents/students affected by pulmonary TB to prevent transmission to other students/students.Key Word : Pulmonary tuberculosis